Digital Forensics And The Admissibility Of Electronic Evidence In Malaysian Syariah Courts: Towards A Standardised Legal Framework - Mohamad Aniq Aiman Alias; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Hasnizam Hashim; Tuan Muhammad Faris Hamzi Tuan Ibrahim (Universiti Sains Islam Malaysia, 2026)
Non-Indexed Publication